The Application of Good Corporate Governance to Online Businesses Based on The Consumer's Point of View - Arda Raditya Tantra (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2021)
The purpose of this study is to describe consumer perceptions of the application of Good Corporate Governance in business online. Consumer perceptions obtained from experiences that have been carried out in shopping online because of the shopping system online that cannot meet the seller directly and cannot see the items to be purchased directly so that confidence is needed to ensure consumers buy goods online. Respondents in this study are consumers who generally have done shopping online. Sampling in this study was random. The data analysis used descriptive statistical analysis and frequency distribution analysis. The results showed that the respondents on average gave answers that the application of the principles of Good Corporate Governance with five dimensions transparency, accountability, responsibility, independence, and fairness has been implemented by the business system online properly.